Snakes in the grass - Everard, Patrick 1967- (Diliman,Quezon City University of the Philippines Press, 2021)
Snakes in the Grass tells the dramatic and often disturbing story of life within the palace walls of Malacanang--home to Imelda and Ferdinand Marcos. This intriguing tale begins with murder and ends with murder. In a frightening twist of fate, Saduj, a young orphan, unwittingly gets caught up in the surreal and sinister Marcos dictatorship. Through his narration we follow the formidable rise of an elite student to president and eventual pariah. Privy to the inner dealings of both Ferdinand and Imelda, Saduj is at first flattered and proud to be such a close confidante of the president, but slowly over time he witnesses the true suffering caused by the barbaric regime. As it slowly dawns on him that he has been hoodwinked into some outlandish fairy tale, so does the chilling reality that he is now a target. With his own life in danger both within the palace walls and on the outside, and the dictatorship about to implode, can he survive long enough to find a way out? Although a work of fiction, the novel is based on true events, and in particular on one exceptional man, destined for greatness but only to end up diseased by power and greed whilst ably abetted by his duplicitous wife.
Keywords: Philippine fiction (English)